Neurofibromatosis Type 1 with Bladder Involvement - Iyimser Üre; Serhat Gürocak; Ipek Isik Gönül; Sinan Sözen; Nuri Deniz (Case Reports in Urology)
Neurofibromatosis type 1 is an autosomal dominant transmitted disease with various clinical manifestations. The bladder is the most commonly affected organ in the genitourinary system. The malignant transformation of the disease is rare, and unlike malign tumors, the treatment option for benign disease is usually conservative. The size and localization of the mass determine the symptoms, most of which are usually not specific. In this paper, we aim to present a 15-year-old patient with neurofibromatosis type 1 with bladder involvement. The clinical presentation and treatment options of this disease are discussed in the light of the literature.